2014
DOI: 10.7202/1026876ar
|View full text |Cite
|
Sign up to set email alerts
|

Chevauchement entre les trajectoires de jeu et les trajectoires de consommation de psychotropes au début de l’adolescence : une étude longitudinale génétiquement informative

Abstract: L’objectif de cette étude est triple : 1- déterminer le nombre, la forme et le degré de chevauchement des trajectoires types de participation à des jeux de hasard et d’argent (JHA) et de consommation de substances psychotropes (SUP) chez un échantillon de jumeaux au début de l’adolescence ; 2- vérifier les ressemblances et les différences au niveau de l’architecture génétique et environnementale des trajectoires de JHA et de SUP ; 3- déterminer la présence de facteurs de risque associés de manière prédictive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Sanscartier, Jiang, & Keough, 2019). For example, using trajectory analysis with samples of participants from early to mid and late adolescence, results of studies from Vitaro et al (2004), Dussault et al (2013), andBilevicius et al (2019) identified two and three pathways of gambling participation with, in all research, the presence of a chronic high group. In line with the pathway model proposed by Blaszczynski and Nower (2002), results from another recent study (Allami et al, 2017) showed that adolescent gamblers can be distinguished in subgroups based on various indicators, such as impulsivity, depression, and drug/alcohol consumption.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sanscartier, Jiang, & Keough, 2019). For example, using trajectory analysis with samples of participants from early to mid and late adolescence, results of studies from Vitaro et al (2004), Dussault et al (2013), andBilevicius et al (2019) identified two and three pathways of gambling participation with, in all research, the presence of a chronic high group. In line with the pathway model proposed by Blaszczynski and Nower (2002), results from another recent study (Allami et al, 2017) showed that adolescent gamblers can be distinguished in subgroups based on various indicators, such as impulsivity, depression, and drug/alcohol consumption.…”
mentioning
confidence: 99%
“…A consistent limitation of all these studies is that they all treated gambling as a homogeneous phenomenon, without considering the (potential) presence of distinctive subgroups based on their level of risk or gambling activity. From this perspective, results from some studies suggest that gambling among adolescents is not a homogeneous phenomenon and that some subgroups can be distinguished in terms of frequency of participation (Dussault et al, 2013; Vitaro, Wanner, Ladouceur, Brendgen, & Tremblay, 2004), variety of gambling activities (Carbonneau, Vitaro, Brendgen, & Tremblay, 2015), severity of gambling problems (Carbonneau et al, 2015; Dussault et al, 2016), and the presence of co-occurring problematic conditions (Allami et al, 2017; Bilevicius, Edgerton, Sanscartier, Jiang, & Keough, 2019). For example, using trajectory analysis with samples of participants from early to mid and late adolescence, results of studies from Vitaro et al (2004), Dussault et al (2013), and Bilevicius et al (2019) identified two and three pathways of gambling participation with, in all research, the presence of a chronic high group.…”
mentioning
confidence: 99%
See 1 more Smart Citation